2003
DOI: 10.1577/1548-8659(2003)132<0605:ptfcsp>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Photographic Techniques for Characterizing Streambed Particle Sizes

Abstract: We developed photographic techniques to characterize coarse (>2‐mm) and fine (≤2‐mm) streambed particle sizes in 12 streams in Anchorage, Alaska. Results were compared with current sampling techniques to assess which provided greater sampling efficiency and accuracy. The streams sampled were wadeable and contained gravel—cobble streambeds. Gradients ranged from about 5% at the upstream sites to about 0.25% at the downstream sites. Mean particle sizes and size‐frequency distributions resulting from digitized ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 16 publications
2
30
1
Order By: Relevance
“…These methods typically rely on photographs of the bed. Also called photosieving, they involve taking plan view images of gravels either in exposed areas [Adams, 1979;Ibbeken and Schleyer, 1986;Butler et al, 2001a] or shallow submerged areas [Whitman et al, 2003]. Generally, images of the riverbed are collected from standing position with some form of scale information in each image.…”
Section: Introductionmentioning
confidence: 99%
“…These methods typically rely on photographs of the bed. Also called photosieving, they involve taking plan view images of gravels either in exposed areas [Adams, 1979;Ibbeken and Schleyer, 1986;Butler et al, 2001a] or shallow submerged areas [Whitman et al, 2003]. Generally, images of the riverbed are collected from standing position with some form of scale information in each image.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a photographic approach is particularly appropriate for fisheries and monitoring applications because, unlike conventional measurement techniques, it is non-invasive, preserving the substrate that is being studied. Whitman et al (2003) found a significant difference between the grain-size distributions and mean particle sizes determined by their photographic technique and Wolman sampling at five sites (as determined by Kolmogorov-Smirnov and t-tests). These results are confirmed by their Figure 3a, which shows a clear difference between the grain-size distributions obtained by the two techniques for a single site.…”
mentioning
confidence: 93%
“…In contrast, all of the grains recorded in the Wolman samples are larger than 8 mm (their Figure 3a). It is therefore unsurprising that the grain-size distributions and mean particle sizes, reported by Whitman et al (2003), are different. Whitman et al (2003) may have retained different lower size limits in their analysis to highlight the bias against fine material that is inherent in Wolman sampling (Fripp and Diplas 1993).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…As an alternative, photogrammetric techniques have been applied for the quantification of grain size parameters since at least the 1970s, especially in river channel hydraulics (Adams, 1979;Ibbeken and Schleyer, 1986;Whitman et al, 2003;Graham et al, 2005a). Many previous photogrammetric studies of sediment grain sizes have involved manually outlining sediment grains on the digital image (Ibbeken and Schleyer, 1986;Ibbeken et al, 1998;Whitman et al, 2003), although, more recently, the focus of photogrammetric studies has been on automating grain detection and data generation (Butler et al, 2001;Sime and Ferguson, 2003;Graham et al, 2005a). In protected, relatively undisturbed areas, such as Marion Island which has Special Nature Reserve conservation status, it is desirable to use techniques such as these photogrammetric methods as they minimise disturbance to the environment.…”
Section: Introductionmentioning
confidence: 99%